Use of artificial intelligence technologies in the development of the Belarusian agro-industrial complex: sociological analysis - Sakovich, Anzhela Yu. (Journal of the Belarusian State University. Sociology, 2025)
The article presents a sociological analysis of the possibilities of use of artificial intelligence (AI) technologies in the development of the Belarusian agro-industrial complex. The analysis is based on the results of a survey of 10 managers and specialists of agricultural enterprises in Miadzel district of Minsk region of the Republic of Belarus, conducted by the author in July – August 2024 using the in-depth interview method. It was revealed that the experts positively assess the prospect of introducing AI technologies in the agricultural industry. The urgency of the problem of providing agricultural enterprises with human resources has been established. It was determined that, in the opinion of respondents, AI technologies will significantly facilitate the labour of agrarians, allow attracting personnel, including young ones, to the agro-sphere, increase its prestige, reduce the need for personnel in agricultural enterprises and increase the economic efficiency of the agro-industrial complex. It is noted that AI is of particular interest to young agrarians. It is pointed out that experts have no concerns about the replacement of human labour by AI technologies in agriculture. The following disadvantages of the introduction of AI technologies in the agricultural industry were named: the unpreparedness of the older generation of farmers to use them in agricultural enterprises, the high cost of maintenance of these technologies and the threat of environmental pollution. It is stated that in order to overcome the difficulties arising from the use of AI technologies in the agrosphere, a comprehensive approach based on the integration of the spheres of information technologies and agriculture is required. It is proposed to create in each farm departments of specialists in the field of information technology, which will monitor the technical serviceability of AI.